2017
DOI: 10.1128/msphere.00329-16
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Lysis through Interference with Peptidoglycan Synthesis Increases Biofilm Formation by Nontypeable Haemophilus influenzae

Abstract: Most, if not all, bacteria form a biofilm, a multicellular structure that protects them from antimicrobial actions of the host immune system and affords resistance to antibiotics. The latter is especially disturbing with the increase in multiresistant bacterial clones worldwide. Bacterial biofilm formation is a multistep process that starts with surface adhesion, after which attached bacteria divide and give rise to biomass. The actual steps required for Haemophilus influenzae biofilm formation are largely not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In order to test this hypothesis further, we sequentially deleted each rpf gene to create a panel of mutants, none of which displayed any growth defects in broth. Hence, to further probe Rpf function, we tested the ability of rpf-defective mutants to form biofilms, given the demonstrated role of PG hydrolases to modulate biofilm formation/maturation in other bacteria (16,17,51). Assessment of the transcript levels of rpf genes in biofilms formed by the wild type after 7, 14, and 28 days revealed that rpfE2 and rpfE were highly expressed in biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In order to test this hypothesis further, we sequentially deleted each rpf gene to create a panel of mutants, none of which displayed any growth defects in broth. Hence, to further probe Rpf function, we tested the ability of rpf-defective mutants to form biofilms, given the demonstrated role of PG hydrolases to modulate biofilm formation/maturation in other bacteria (16,17,51). Assessment of the transcript levels of rpf genes in biofilms formed by the wild type after 7, 14, and 28 days revealed that rpfE2 and rpfE were highly expressed in biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…HITS was also useful to identify H. influenzae genes required to colonize an influenza A virus (IAV) co-infection murine model, showing genes both exclusive or commonly shared by bacterial and IAV co-infection model systems [67] , or to screen genome-wide genetic interactions to unravel epistatic interaction accounting for H. influenzae survival in the murine lung [68] . Tn-seq suitability has also been reported for H. influenzae in vitro genome-wide screening studies including the identification of (i) essential genes [69] ; (ii) the carbonic anhydrase involvement in NTHi adaptation to changes in environmental CO 2 levels and intracellular survival [70] ; (iii) a role for the outer membrane protein P5 in NTHi survival to complement-mediated killing [71] , and for galactose-containing oligosaccharide structures in NTHi survival to complement-dependent neutrophil-mediated killing [72] ; (iv) the contribution of the mltC and lppB genes to biofilm formation [73] .…”
Section: Constantly Evolving Information From H Influenzae Whole Genome Sequencingmentioning
confidence: 99%
“…HITS* based in vivo genetic screenings [12] , [67] , [68] B2. Tn-seq based in vitro genetic screenings [69] , [70] , [71] , [72] , [73] C. Genome-wide gene expression profiling C1. Bacterial transcriptomic responses to changing environmental conditions [75] , [76] , [77] , [78] , [79] , [82] , [84] , [87] C2.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse classes of antimicrobials have been analyzed to determine their effects on bacterial physiology. For instance, beta-lactam antibiotics that inhibit cell wall biosynthesis have been found to increase biofilm formation, while antimicrobials such as fluoroquinolones targeting specific cellular functions like DNA replication may decrease formation (Marti et al, 2017; Ranieri et al, 2018; Yu et al, 2018). Likewise, some antimicrobials can alter bacterial cell surface properties such as ionic charge and cause more favorable conditions for adherence and biofilm formation (Kumar and Ting, 2013; Kumar and Anthony, 2016; Ranieri et al, 2018).…”
Section: Antimicrobials As a Weapon Or A Toolmentioning
confidence: 99%